EFFECTIVENESS OF THE PREVENTIVE ACTIONS OF THE MALE AND FEMALE BREAST CANCER IN THE MUNICIPALITY OF GUARULHOS (Fiep Bulletin - online, 2016)
Objective: Check whether the actions of prevention of Breast Cancer are being effective. Methods: The method of approach used was the deductive. The instrument of the data queue was formed from a questionnaire with two parts, drawn up for the purposes of this study. The queue of data was performed by means of questionnaire. Results: The results showed that the average age of respondents included in the analysis of female sex was 51.1 years, and 54.8 years for males. In relation to ways of detecting breast cancer, 100% of women know to detect it and know the self-examination of breasts, in relation to men, 24% do not know the ways to detect breast cancer, and 40% do not know the car review. In relation to the realization of the self breast exam, 58% of those interviewed female, carried out it, being that the male sex, 100% do not perform it; 98% of women and 74% of the men, known to prevention activities in the health units; 78% of women, were examined by a professional and 100% of the men, were not. Conclusion: The data obtained from this study showed that the majority of the interviewed knows to detect and know the self-examination and breast cancer prevention activities carried out in the health unit; they received information about the breast cancer in the past two years, having received this orientation by means of communication. Female respondents received guidance from a health professional about prevention of breast cancer, whereas no interviewed male receipt guidelines. The most unknown to the services offered by the municipality relating to the prevention of breast cancer, and most have access to the services offered by the municipality and use it to make medical consultations.
Keywords: Cancer; Breast; Actions to Prevent